REaCH-Resiliency Engagement and Care in Health; a Befriending Intervention to Address the Psycho-Social Challenges of Vulnerable Youth in the Context of COVID-19 Pandemic: An Exploratory Trial in India - Saju Madavanakadu Devassy (MDPI AG, 2021)
The study explores the effectiveness, feasibility, and acceptability of a befriending intervention delivered by trained lay health workers to address the issues of the rural youth during the COVID-19 pandemic. We did an exploratory trial with 501 upskilled youth, where we randomly recruited 251 to the intervention group (REaCH) and 250 to the control group (General Enquiry Telephone Call-GETC). The outcome variables included in the study were depressive symptoms, wellbeing, and social support. The majority of the participants were females (64.2%), unmarried (63.55%), and hailed from economically poorer households (57.63%). The befriending intervention reduced depressive symptoms (OR: 0.95, p = 0.05) and significantly improved social support (OR: 1.03, p = 0.000) among participants in the intervention group. The participants in the intervention group had higher perceived social support from friends, families, and significant others when compared to the control group. Additionally, suicidality scores decreased for people in the intervention group from baseline to follow up; however, the results were not statistically significant. Befriending intervention is a practical, low-cost technique to sustain the youth in employment and ensure sustainable income. It inspires practitioners and policymakers to create mental health gatekeeping. The trial was registered prospectively on 27 July 2020 in Clinical Trial Registry India; ICMR-NIMS (Registration Number: CTRI/2020/07/026834).